'Attentive movement' as a method for treating depression. Issue 1 (2nd January 2019) - Federman, Dita; Shimoni, Shalev; Turjeman, Nataly
ABSTRACT: The objective of this study was to examine whether 'attentive movement', is an effective method for treating depression. A quantitative research methodology design was used. Fifty participants took part in attentive movement group therapy sessions once a week for 12 weeks. All completed the Beck Depression Inventory (BDI) and a demographic questionnaire. A mixed-design ANOVA was performed; the between-group variables included the study groups (control/experimental) and the within-test group comparison examined measurement time (time1/time2).Results revealed a significant effect for measurement time (F (1, 44) = 27.78, p < .001), which indicated a significant reduction in the symptoms of depression from the first measurement (M = .98, SD = .39) to the second measurement (M = .72, SD = .50). The level of depression following treatment in the experimental group was significantly lower than in the control group. The research hypothesis was confirmed.